Peran Propam Dalam Menangani Oknum Anggota Polri Yang Terlibat Tindak Pidana Peyalahgunaan Narkotika dan Penerapan Peraturan Pemerintah Nomor 03 Tahun 2003 Tentang Pelaksanaan Institusional Teknis Peradilan Umum Bagi Anggota Polri di Wilayah Hukum Polres Batanghari - Syarifuddin, Amir; Sarbaini, Sarbaini; Delliansyah, Eflan (Universitas Batanghari Jambi, 2023)
The abuse and circulation of Narcotics has now penetrated to the point where all groups become victims. Not only ordinary people or teenagers who have become victims of narcotics abuse, even police officers who incidentally are law enforcers who are supposed to eradicate the illicit traffic of narcotics are actually involved in narcotics abuse. the existence/or role of Propam POLRI is very much needed in carrying out various legal actions against individual members of the Police who are involved in Narcotics abuse. The issues discussed in this thesis are: The Role of Propam in Managing Police Members involved in Narcotics Abuse in the Legal Area of the Batang Hari Police , Application of Government Regulation Number 03 of 2003 Concerning General Court Technical Implementation for Individual Police Members involved in Narcotics Abuse in the Legal Area of the Batang Hari Police, and Obstacles to efforts made in overcoming the obstacles encountered. Research Methodology yuridis empiris, Approach Used Law Approach, Conceptual Approach and Case Approach, research findings: 1. Role of Propam in managing Individual Police Members those involved in Narcotics Abuse in the Legal Area of the Batang Hari Police, this has been implemented. This can be seen from cases of narcotics use involving unscrupulous members of the National Police for the last 3 (three) years, namely from 2020 to 2022 as many as 9 (nine) cases were successfully resolved, 2 The application of Government Regulation Number 03 of 2003 concerning the Technical Implementation of General Courts for Police Members involved in Narcotics Abuse in the Legal Area of the Batang Hari Police has been implemented, this can be seen from the 9 (nine) members of the Batang Hari Police who have been involved in the use of narcotics for three the last year, namely from 2020 to 2022, the provisions of Government Regulation Number 03 of 2003.